Human rights approach to environmental protection with special reference to the Niger Delta of Nigeria - Abdulkadir, Bolaji Abdulkadir (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2014)
The protections of environment and human rights are among the foremost concerns of international community. Towards the end of twentieth century, the linkages between the protection of human rights and environment began to manifest. Since then, there has been increasing awareness and acknowledgement of the correlation between the two subjects. The degradation of the Niger Delta environment from petroleum activities has led to the incidences of human rights violations notwithstanding the adoption of human rights treaties and fundamental human rights in the Nigerian Constitution. This has led to the violation of the right to life, right to the enjoyment of property, access to clean water, and the right to a clean and healthful environment. Therefore, this thesis examines the relationship between human rights and the environment as an attempt to show the indivisibility of the two fields. It seeks to discover how environmental degradation affects the enjoyment of basic human rights to the people of Niger Delta Region. The research-work also assesses the effectiveness or otherwise of the legal framework on environmental protection in Nigeria. This is done through the examination of the constitutional status on environment and arrays of legislations dealing with environment. Also, the thesis assesses the effectiveness of tort law remedies to environmental dispute and justice system in Nigeria. It also explores how human rights provisions can be used to protect the environment. This was done through the examination of substantive and procedural rights such as the right to life, equality right, right to property, right of access to information and right to participation that have been found to be of immense use in the pursuit of environmental justice. The thesis primarily adopts qualitative method of research, which involves both doctrinal and non-doctrinal legal research. On this note, the research work finds the existing laws on environment in Nigeria to be weak and insufficient and this underscores the unsatisfactory performance of the regulatory bodies. This thesis also finds that judicial creativity and wisdom have shown that there are a number of benefits of using human rights provisions than other available remedies in the quest for environmental protection and justice. As a result of these findings, the research work suggests some recommendations in order to reinforce the legal frameworks and improve environmental justice. Also, important recommendations are made to both the government and the public so as to enhance access to environmental justice and promote human rights.